Association of 5, 10- methylenetetrahydrofolate reductase C677T polymorphism in susceptibility to tropical chronic pancreatitis in north Indian population - Singh, S.; Choudhuri, G.; Kumar, R.; Agarwal, S. (Cellular and Molecular Biology, 2012)
MTHFR is a key enzyme in folate metabolism that catalyzes the conversion of 5, 10-methlenetetrahydrofolate (5, 10- methylene THF) to 5-methyltetrahydrofolate (5-methyl THF), a predominant circulatory form of folate and methyl donor for the remethylation of homocysteine to methionine. Some studies have shown that C667T polymorphism increases the risk of pancreatic cancer. Since MTHFR is involved in methylation, inflammation and protection against oxidative stress, the processes especially important for pancreatic homeostasis. The altered enzyme activity could play a role in pancreatic injury. The role of MTHFR C677T polymorphism in chronic pancreatitis has been explored by conducting a hospital based; case-control study involving 100 patients radiologically confirmed chronic pancreatitis and 329 healthy controls. All samples were analyzed for MTHFR C677T polymorphism using PCR-RFLP method. Restriction enzyme Hinf I was used to digest the 198 bp amplified product. The frequency of the MTHFR was 57.3%, 34.1% and 8.5% among cases compared with 87.2%,11.2% and 1.5% of controls for CC, CT and TT genotypes, respectively. The T Allele frequency was found significantly higher in patients than in controls. A significant association with T allele was observed with p-value (< 0.0001) odds ratio 4.475 and (95% CI=2.961-7.046). It could be predisposing to the traditional risk factors such as diabetes, dietary, alcohal and smoking habit that are known to be associated with chronic pancreatitis. Additionally it was observed that smoking increases the risk of chronic pancreatitis by 4.1 times. The T allele frequency of MTHFR (C667T) was found to be a significant risk factor for chronic pancreatitis playing a crucial role in altered folate metabolsim.